Circulating Tumour DNA for Early Diagnosis of Pancreatic Ductal Adenocarcinoma - Ayu Hutami Syarif (Indonesian Journal of Cancer, 2021)
Background: Pancreatic ductal adenocarcinoma (PDAC) has been deathly cancer arising from pancreatic cells. Despite the improvement in the standard of diagnosis, most patients seek medical care in the late stage. Due to the aggressiveness of the disease, it is therefore imperative to detect the early lesion for a better outcome.Methods: We identified 416 articles relevant to circulating tumor DNA (ctDNA) and PDAC using predefined keywords in PubMed, PubMed Central, and Cochrane Library from January 1, 2011, to January 1, 2021 (10 years). Firstly, we screened the titles and abstracts, and 63 articles were included. Then, we screened those articles for the full-text version and included only 8 articles fulfilling our inclusion criteria. All steps were reviewed by the author.Results: The presence of ctDNA in the blood reflects the occurrence of the pancreatic cancerspecific mutation in the primary tumor. The detection of KRAS mutation in ctDNA and tumor samples is highly consistent. The number of positive findings in early-stage patients is low, in line with the low ctDNA concentration measured. However, the combination of KRAS detected in ctDNA and other biomarkers showed prominent results with higher sensitivity and specificity.Conclusions: ctDNA is a promising tool for early detection of PDAC. Despite its low positivity rate in certain studies, it is considerably concordant with the primary tumor. Future improvement in the technique application is required to overcome the issue of low DNA concentration in circulation.